Echocardiographic predictors of neonatal illness severity in fetuses with critical left heart obstruction with intact or restrictive atrial septum. (16th July 2018) - Gellis, Laura; Drogosz, Monika; Lu, Minmin; Sleeper, Lynn A.; Cheng, Henry; Allan, Catherine; Marshall, Audrey C.; Tworetzky, Wayne; Friedman, Kevin G.
Abstract: Background: Neonates with critical left heart obstruction and intact atrial septum (IAS) or restrictive atrial septum (RAS) are at risk for hypoxia within hours of birth and remain a group at high risk for mortality. Methods: Prenatally diagnosed fetuses with critical left heart obstruction and IAS or RAS with follow‐up from January 1, 2005, to February 14, 2017, were included. Primary outcome was a composite measure of severe neonatal illness (pH < 7.15, venous pH < 7.10, bicarbonate < 16 mmol/L, lactic acid > 5 mmol/L, or median oxygen saturation < 60% within 2 hours of birth). Results: Of 68 live born fetuses, 52 (76.5%) had hypoplastic left heart syndrome, 14 (20.5%) had critical aortic stenosis, and two (3%) had complex anatomy with mitral stenosis/atresia. There were 27 (39.7%) fetuses with IAS and 41 (60.3%) with RAS. Severe neonatal illness was present in 36 (52.9%). The strongest discriminators for severe neonatal illness were a pulmonary vein A:R VTI ≤ 2.7 ( P < 0.001, AUC 0.93) and larger pulmonary vein diameter ( P = 0.025, AUC 0.77). A:R VTI ≤ 2.7 predicted death or transplant (log‐rank P = 0.03). Conclusions: In neonates with hypoplastic left heart syndrome and IAS or RAS, A:R VTI ≤ 2.7 is predictive of severe neonatal instability. This threshold can help guide resource planning, delivery management, and improve fetal intervention criteria. Abstract : What is already known on this topic? Hypoplastic left heart syndrome (HLHS) with intact or restrictive atrial septum continues to be a subset of patients with high mortality despite advances in surgical and medical management. Prior studies in small cohorts (n 8) have suggested that fetal pulmonary venous Doppler flow patterns are altered in HLHS with intact or restrictive atrial septum and can be predictive of emergent postnatal intervention to decompress the left atrium. What does this study add? In a larger cohort of patients with HLHS and intact or restrictive atrial septum, this study finds that on both mid and late gestation echocardiograms, pulmonary vein size and Doppler patterns are highly predictive of severe neonatal illness and can risk stratify fetuses for severe neonatal illness as well as need for emergent intervention. Fetal intervention on the atrial septum improves pulmonary venous Doppler indices.